2019
DOI: 10.1038/s42003-019-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and mapping the universe of evolutionary graphs identifies structural properties affecting fixation probability and time

Abstract: Population structure can be modeled by evolutionary graphs, which can have a substantial influence on the fate of mutants. Individuals are located on the nodes of these graphs, competing to take over the graph via the links. Applications for this framework range from the ecology of river systems and cancer initiation in colonic crypts to biotechnological search for optimal mutations. In all these applications, both the probability of fixation and the associated time are of interest. We study this problem for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 39 publications
5
74
2
1
Order By: Relevance
“…High (low) temperatures generally enhanced (suppressed) the strength of selection. This observation agrees with other results of evolutionary graph theory, see, for example, [21, 22,58] In particular, finding these temperatures provides a computationally efficient method of estimating the mutant fixation probabilities [79], and it may potentially lead to some general analytical insight. The mean temperature was also a good predictor of the fixation probabilities for a territorial raider model in [23].…”
Section: The Framework Of Broom and Rychtář: The Full Dynamic Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…High (low) temperatures generally enhanced (suppressed) the strength of selection. This observation agrees with other results of evolutionary graph theory, see, for example, [21, 22,58] In particular, finding these temperatures provides a computationally efficient method of estimating the mutant fixation probabilities [79], and it may potentially lead to some general analytical insight. The mean temperature was also a good predictor of the fixation probabilities for a territorial raider model in [23].…”
Section: The Framework Of Broom and Rychtář: The Full Dynamic Modelsupporting
confidence: 89%
“…Hindersin and Traulsen [40] studied the effect of edge removal on the fixation time, which was robust to the removal even of a large number of edges. Möller et al [58] carried out a numerical study which also supported the robustness of evolutionary graph properties to structural change. We note that there will be some situations where changes to structure can have a big effect, for example specific graphs like the star that are subject to vertex or edge removal, as this will make the graph unconnected.…”
Section: Game and Dynamics Parametersmentioning
confidence: 89%
See 1 more Smart Citation
“…There is a growing interest in the design of networks that optimize probabilities and times of spread of advantageous mutations in a population (for example in experimental evolution or for biotechnological applications), or the spread of cultural information (or misinformation) across social networks (Lieberman et al, 2005;Möller et al, 2019). Our results provide a general predictive theoretical framework for understanding the relevant network statistics for a population's future evolutionary dynamics.…”
Section: Introductionmentioning
confidence: 81%
“…The main findings are that generally fixation probability and fixation time is correlated such that a higher fixation probability comes with a higher fixation time. Within this general rule, it has further been shown that generalized stars maximize fixation probability while minimizing fixation time, while comet-kites minimize fixation probability while maximizing fixation time [18]. Furthermore, if we allow self loops and weighted links, we may construct arbitrarily strong amplifiers of selection [25].…”
Section: Introductionmentioning
confidence: 99%